Buses and Branch Performances Considering Load Changes of The 150 kV Transmission Line in Malang Area - Afina, Nimas; Afandi, A.N.; Fujita, Goro (Frontier Energy System and Power Engineering, 2020)
This paper examines the power flow based on load value conditions that have ascended in the 150 kV transmission system in the Malang Area. Simulations are carried out for several regions that may experience ascension load values. The simulation results show a significant change at some points, especially when the value of the load ascension is 25%. Whereas the ascension of 8.6% is not too significant considering this value is based on the production planning. These changes occur in the bus and branch of the 150 kV transmission lines which is needed for a network interconnection in the electricity system of Malang Raya as an effort to keep the ascension capacity and reliability, and to improves the quality of service to consumers.